The Diagnostic Values of Pretreatment Serum Inflammation Markers and Lipoprotein in Men With Total Prostate-Specific Antigen Between 4 and 10 ng/ml - Li, Guangping; Shang, Zhenhua; Liu, Yihao; Yan, Hao; Ou, Tongwen (Frontiers in Medicine, 2020)
Background The purpose of this study was to analyze the values of pretreatment serum inflammation markers, lipid and lipoprotein for predicting the pathological results in men with total prostate-specific antigen between 4 and 10 ng/ml. Materials and method 611 eligible patients diagnosed with total prostate-specific antigen between 4 and 10 ng/ml and who received transrectal ultrasound-guided prostate biopsy between January 2014 and December 2019 were included in our study. All the patients were divided into groups according to the pathological results and we collected the data of their pretreatment indicators of the blood routine and biochemistry. Results The pathological results from prostate biopsies comprised 160 patients with prostate cancer and 451 patients with benign lesions. Age and total prostate-specific antigen values were significantly higher in patients with prostate cancer than those with benign lesions (P<0.05). Red blood cell, platelet count, prealbumin and triglyceride were significantly lower in patients with prostate cancer than those with benign lesions. Neutrophil–lymphocyte ratio, platelet–lymphocyte ratio, lymphocyte- monocyte ratio, apolipoprotein B were lower and apolipoprotein A-I was higher in the prostate cancer group than in the benign lesions group but not significant (P>0.05). Multivariate logistic regression revealed age and total prostate-specific antigen could be independent predictors for pathological results (OR, 1.064, 95%CI, 1.031-1.098, P<0.001; OR, 1.232, 95%CI, 1.061-1.429, P=0.006). Conclusion: Higher age and total prostate-specific antigen were closely related to the pathological results. Prospective studies conducted with large patients are needed to evaluate the diagnostic value of noninvasively pretreatment serum inflammation markers and lipoprotein for predicting the pathological results in men with total prostate-specific antigen between 4 and 10 ng/ml.